Israel : Report on the Observance of Standards and Codes-Monetary and Financial Policy Transparency, Banking Supervision, Securities Supervision, and Payment Systems-Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper presents an update to the Report on the Observance of Standards and Codes Fiscal Sector Modules for Israel. The 2000-01 Financial Sector Assessment Program mission assessed Israel's compliance with the Basel Core Principles for effective banking supervision. Israel was found materially noncompliant because of secrecy provisions that prohibit the Bank of Israel from disclosing supervisory information to other supervisors, both domestic and international. Israel was also found not fully compliant in some other areas including: objective, autonomy and powers; loan evaluation and loan loss provisioning; and investment criteria.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: BOI Governor; CR; ISCR; Rule; SC; Israel